The Effect of Neurological Impress Method (N.I.M) on Reading Ability of English Text on Dyslexic Students - Salila Prasidya Hidayati; Fahri Fahri (Eduvest - Journal of Universal Studies, 2021)
This study aims to find out the effect of the neurological impress method on the reading ability of English text on dyslexic students, including phonemic awareness, reading fluency, and reading comprehension. This study intends to determine the use of the neurological impress method to boost the reading ability of dyslexic students in Galuh Handayani Inclusive School Surabaya. The participants of this study are three dyslexic students and two teachers. The data were collected through observation and interview and analyzed by using the descriptive qualitative method. In short, this study supports the use of the neurological impress method to develop the reading ability of English text as a foreign language on students with learning disabilities. According to the observation and interview that have done by the researcher in Galuh Handayani Inclusive School Surabaya, it can conclude that the neurological impress method is the method that appropriates for increasing the reading ability of dyslexic students.